Measuring The Influence of The Human Development Index, Foreign Investment, Domestic Investment, and Labor Force on Economic Growth in Banten Province - Aisyah, Siti Nur; Santosa, Purbayu Budi (Journal of Economic Education, 2024)
This research aims to analyze the influence of the human development index, foreign investment, domestic investment, and labor force on economic growth in Banten Province. This research is quantitative research using panel data for the period 2018 - 2022 with observations of eight districts/cities in Banten Province. The analysis method used is panel data regression. Based on the model selection test with the Lagrange multiplier, the results showed that the random effect model was the right model to be used in this research. The results of hypothesis testing using the t test show that partiallyThe human development index variable has a positive and significant effect oneconomic growth with a coefficient of1.087203.The foreign investment variable has a positive but not significant influence on economic growth with a coefficient of0.027156. The domestic investment variable has a positive and significant effect oneconomic growth with a coefficient of0.003893. The labor force variable has a positive and significant effect oneconomic growth with a coefficient of2.190287. This research has a limited number of research variables and the scope of the research area so that further research can add variables and a wider area.